Pete the Cat's 12 groovy days of Christmas - Dean, James 1957-; Dean, Kim 1969- (New York : Harpercollins Childrens Books, 2018)
Pete and his friends are rockin' and groovin' while counting down the days to Christmas! Who needs five golden rings, when you can have five onion rings?
106435
Keywords: Pete -- the Cat (Fictitious character) -- Juvenile fiction; Gifts -- Juvenile fiction; Picture books; Christmas fiction; Animal fiction; Christmas fiction; Picture books